General methodologies to virtualize FPGAs in Hw/Sw systems - Fornaciari, W.; Piuri, V. (Circuits and Systems; Proceedings: Midwest Symposium on Circuits and Systems, 1998)
The computational needs of an increasing number of applications often require dedicated circuits. Configurable devices, like the Field-Programmable Gate Arrays (FPGAs), are one of the most used solutions to implement such a hardware support. However the size of the circuits that can be mapped on the currently available FPGAs at a medium or low cost is limited with respect to the high demand of several applications in particular when embedded systems and single-chip systems are concerned. This paper introduces some operating-system techniques (namely, partitioning and overlaying) to virtually enlarge the size of the FPGA from the point of view of the applications. The solutions mimic the approaches widely used in the operating systems for virtual memory.